2011
DOI: 10.1021/es201498v
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Metallic Coagulants on the Removal of Organic Compounds from Oil Sands Process-Affected Water

Abstract: Coagulation/flocculation (CF) by use of alum and cationic polymer polyDADMAC, was performed as a pretreatment for remediation of oil sands process-affected water (OSPW). Various factors were investigated and the process was optimized to improve efficiency of removal of organic carbon and turbidity. Destabilization of the particles occurred through charge neutralization by adsorption of hydroxide precipitates. Scanning electron microscope images revealed that the resultant flocs were compact. The CF process sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 44 publications
6
79
0
Order By: Relevance
“…Although many different treatments have been investigated for their ability to remove NAs from OSPW, most of the approaches have shown poor efficiency for removal of the most recalcitrant compounds. Additionally, the relatively high costs of many of these treatments may limit their applications in large-scale industrial treatments (Kim et al 2011;Pourrezaei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although many different treatments have been investigated for their ability to remove NAs from OSPW, most of the approaches have shown poor efficiency for removal of the most recalcitrant compounds. Additionally, the relatively high costs of many of these treatments may limit their applications in large-scale industrial treatments (Kim et al 2011;Pourrezaei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The combination results in charge neutralization and instability in aqueous solution. While coagulation/flocculation has often been investigated for the improved setting of dissolved fine solids in OSPW [82][83][84], in some circumstances, it has also been shown to be an effective method for NA removal [85,86].…”
Section: Coagulation/flocculationmentioning
confidence: 99%
“…Pourrezaei et al [85] demonstrated the removal of NAs from OSPW using a coagulation/flocculation process. The OSPW was collected from the West In Pit settling basin operated by Syncrude Canada Ltd in Fort McMurray, Alberta.…”
Section: Coagulation/flocculationmentioning
confidence: 99%
See 1 more Smart Citation
“…A solid addition method was used to determine the pH of the zero surface charge (PZC) of the adsorbent. The AEF concentrations in OSPW before and after adsorption were measured using a FT-IR instrument (PerkinElmer Spectrum, 100 FT-IR Spectrometer, Waltham, USA), following the methodology explained in details elsewhere (Jivraj et al 1996;Pourrezaei et al 2011). …”
Section: Water Quality Analysismentioning
confidence: 99%